Security Challenges of Small States - Baral, Bhimnath (Journal of Political Science, 2017)
The concept of Security has a vital role in the study of international relations. This concept is old as human civilization. It has different meaning in different phases of history. However, there have been sea changes in the interpretation of security matters. The traditional state-centric security has transferred into modern human centric approach. But the small states are always threatened by it in different forms and nature. As a precondition for sustainable political, economic and social development, small states are always tortured by several internal and external factors. So, this article overviews about the various security challenges faced by small states. Journal of Political Science. Vol. 17, 2017, Page: 1-17